2016
DOI: 10.1155/2016/7984576
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Follow-Up of Dexamethasone Implants for Macular Edema from Various Diseases in Vitrectomized and Nonvitrectomized Eyes

Abstract: Purpose. To evaluate the best-corrected visual acuity (BCVA), central retinal thickness (CRT), and the number of dexamethasone implants needed to treat cystoid macular edema (CME) from various etiologies over 12 months in vitrectomized and nonvitrectomized eyes. Methods. This multicenter retrospective cohort study included 112 patients with CME secondary to retinal diseases treated pro re nata (PRN) with a 0.7 mg intravitreal dexamethasone implant for 12 months. The BCVA, CRT, adverse events, safety data, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…28–30 For instance, studies have reported that the concentration of IVTA decreased faster in the vitrectomized eye than in the nonvitrectomized eye, 30 and that vitrectomized eyes needed more dexamethasone implants compared with nonvitrectomized eyes for the treatment of CME of various etiologies (1.35 vs. 3.2 dexamethasone implants). 60…”
Section: Discussionmentioning
confidence: 99%
“…28–30 For instance, studies have reported that the concentration of IVTA decreased faster in the vitrectomized eye than in the nonvitrectomized eye, 30 and that vitrectomized eyes needed more dexamethasone implants compared with nonvitrectomized eyes for the treatment of CME of various etiologies (1.35 vs. 3.2 dexamethasone implants). 60…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is discussed that PPV could lead to more rapid drug diffusion and clearance from the vitreous cavity in vitrectomized eyes, therefore limiting the exposure of intravitreal therapies and reducing the treatment success [7] of therapies such as anti-VEGFs [8,[17][18][19] and maybe even dexamethasone implants [20][21][22][23][24][25][26], although the authors acknowledge that the treatment reg-imen and duration for a dexamethasone implant in vitrectomized eyes still remain controversial [27].…”
Section: Discussionmentioning
confidence: 99%
“… 10 A recent paper reported opposite clinical results in 112 eyes with a significant increase in the required number of implants in vitrectomized eyes at month 12 and that no significantly differences were found in anatomical and functional outcomes. 12 ILUVIEN (Alimera Sciences, Inc., Alpharetta, GA, USA) is a micro-implant, which is constituted by a non-biodegradable matrix made of polyamide. It contains 190 μ g of fluocinolone acetonide (FAc) released during 3 years (0.2 μ g of FAc per day released in the vitreous).…”
Section: Introductionmentioning
confidence: 99%